Интенсификация процесса замешивания дрожжевого теста - Кравченко, Александр Иванович; Рачок, Виталий Викторович; Теличкун, Юлия Станиславовна; Теличкун, Владимир Иванович (My University, 2013)
Замес пшеничного теста имеет целью не только получение однородного и хорошо промешанного во всей массе теста, но и придание ему оптимальных физических свойств. Изучение структурно-деформационных и физико-механических свойств теста имеет большое значение для приготовления полуфабрикатов в производственных условиях способами, основанными на интенсификации процессов брожения. The purpose of the intensification of mixing dough - a homogenous mass, which is characterized by certain rheological properties. Effect of intensive machining dough during kneading the dough to modify the viscosity was studied . The influence of the energy consumed for making dough for the effective viscosity is investigated. It is established that viscosity of dough decreases by linear pattern at increase costs of specific work for knead of dough. During fermentation. the dough which kneaded with varying intensity, there is a further decrease of dough viscosity. Reducing the viscosity of the dough
Keywords: интенсификация; іntensification; смешивания; kneading; смесительная машина; kneading machine; кафедра машин і апаратів харчових та фармацевтичних виробництв